PENERAPAN SANKSI DENDA TERHADAP NASABAH PEMBIAYAAN YANG MENGALAMI NON PERFORMING FINANCING (Bank Pembiayaan Rakyat Syariah Haji Miskin Pandai Sikek) - fadli, elfadhli (JURNAL ISLAMIKA, 2021)
One of the risks faced by banks is the failure to pay installments on time by financing customers. However, some of these failures were caused by force majeure or due to moral hazard. At BPRS Haji Poor Pandai Sikek, every financing customer who fails to pay installments on time is subject to a fine. The purpose of this study was to determine the application of fines to financing customers who experienced non-performing financing at BPRS Haji Miskin Pandai Sikek. The author uses the type of field research (field research) with descriptive qualitative research methods. This study shows that the application of fines to financing customers who experience non-performing financing at the Haji Miskin Pandai Sikek BPRS has not been implemented properly according to the DSN-MUI fatwa no. 17/DSN-MUI/IX/2000. The results showed that the application of fines imposed by BPRS Haji Poor to financing customers was applied to all customers who were late in paying installments. However, the Haji Poor BPRS as the party providing the financing may suspend or waive fines that were originally paid by customers who are unable/unable to pay installments. However, this applies only to customers who always communicate with Islamic banks regarding their financial situation or condition, are open to the problems they face.